1998
DOI: 10.1523/jneurosci.18-04-01595.1998
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Hippocampal Acetylcholine Release and Spontaneous Alternation Scores by Intrahippocampal Glucose Injections

Abstract: Recent evidence indicates that systemic glucose treatment enhances memory while producing a corresponding increase in hippocampal acetylcholine (ACh) output. The present experiments examined whether unilateral intrahippocampal infusions of glucose would enhance spontaneous alternation performance and whether there would be a corresponding increase in ACh output in the ipsilateral and contralateral hippocampus. Extracellular ACh was assessed in samples collected at 12 min intervals using in vivo microdialysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
138
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 197 publications
(158 citation statements)
references
References 42 publications
(48 reference statements)
18
138
2
Order By: Relevance
“…Spontaneous alternation tasks as used in present study have previously been found to elicit ACh release in the hippocampus of rats in a manner related to memory performance on this task (Chang and Gold, 2004;Ragozzino and Gold, 1995;Ragozzino et al, 1996Ragozzino et al, , 1998Pych et al, 2005). The microdialysis results presented here suggest that the onset of dysfunctions in septohippocampal cholinergic functions, i.e.…”
Section: Acetylcholine Releasesupporting
confidence: 56%
See 2 more Smart Citations
“…Spontaneous alternation tasks as used in present study have previously been found to elicit ACh release in the hippocampus of rats in a manner related to memory performance on this task (Chang and Gold, 2004;Ragozzino and Gold, 1995;Ragozzino et al, 1996Ragozzino et al, , 1998Pych et al, 2005). The microdialysis results presented here suggest that the onset of dysfunctions in septohippocampal cholinergic functions, i.e.…”
Section: Acetylcholine Releasesupporting
confidence: 56%
“…The maze had four identical arms (25.5 x 7.7 x 10.0 cm, L x W x H) extending from a central platform (7.7 x 7.7 cm). Mice were allowed to traverse the maze freely as in previous studies with rats (Chang and Gold, 2004;McNay and Gold, 2001;Ragozzino et al, 1996Ragozzino et al, , 1998Pych et al, 2005;Gold, 1998, 2001). After being placed in the central platform, mice were permitted to move freely through the maze for 6 minutes.…”
Section: Spontaneous Alternation Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, on the basis of these results, it appears that glucose administration may facilitate memory by directly increasing hippocampal ACh synthesis in a dose dependent manner. These results were subsequently extended, in that injecting glucose into the hippocampus unilaterally was observed to increase ACh output from both the ipsilateral and contralateral hippocampus (Ragozzino et al, 1998).…”
Section: Ach Synthesismentioning
confidence: 77%
“…We have also found this multimodal brain region to be important in the formation of memory in both passive avoidance and bead discrimination learning paradigms (Gibbs and Ng, 1977;Gibbs and Summers, 2002a). Memory formation is energy dependent and central injection of glucose can modulate memory (Ragozzini et al, 1998;Krebs and Parent, 2005;McNay et al, 2000McNay et al, , 2001. Memory formation can be inhibited by 2-deoxyglucose (DG; Gibbs and Summers, 2002b), which is not metabolized and by DAB (1,4-dideoxy-1,4-imino-D-arabinitol) an inhibitor of glycogen breakdown (Gibbs et al 2006a).…”
Section: Introductionmentioning
confidence: 95%